The Treaty on Conventional Armed Forces in Europe and Russian foreign and security policy - Wilcox, Mark R. (Kansas State University, 2020)
From the time Mikhail Gorbachev signed the CFE Treaty in 1990 until Vladimir Putin abandoned it in 2015, the Soviets and their successors in the Russian Federation showed amazing persistence in their relationship with the “cornerstone of European security.” Unlike earlier proposals by the Soviets for arms control, Moscow’s approach to the CFE Treaty was not just a propaganda ploy, but a genuine attempt to shape the security environment in Europe and the former USSR to create breathing room for the development of the economy. Within this endeavor, the treaty also provided a means to manage the dismantling of the Soviet Union’s large conventional armed forces as they returned from Eastern Europe and transitioned into the armies of the newly independent states of the former USSR. Over time, however, the CFE Treaty proved ineffective in constraining a significant change to the European security landscape, the enlargement of NATO. Simultaneously, Russia’s foreign and security policy evolved, first from that of the Soviet system dominated by the CPSU to the product of the new governing institutions of the Russian Federation; and, second, from one that focused on the domestic development of the country to that of a more confident state that was reasserting itself as a great power, as Putin made clear in his speech to the Munich Security Conference in 2007. Along the way, the CFE Treaty lost its luster, despite Moscow’s dogged engagement with it, and in 2015, the Russians de facto withdrew from it. This dissertation presents a scholarly examination of the CFE Treaty as a factor in Russia’s foreign and security policy. Although the literature is rich in studies of the CFE Treaty and European security, as well as the development and trajectory of Russia’s foreign and security policy, it lacks one that focuses on the treaty’s efficacy as a tool of policy. Drawing extensively on primary sources and analyses by Russian authors (among whom are those who negotiated and implemented the CFE Treaty), this dissertation constructs two historical narratives (CFE Treaty, Russian Security Policy), performs detailed case studies, and employs a conceptual framework to show that over time, while Moscow remained engaged with the CFE Treaty (and the adapted version of it that was negotiated at Moscow’s insistence), undesired effects gradually accrued at the expense of desired effects of this arms control agreement on Russia’s national interests. The expansion of NATO into states near and adjacent to Russia’s borders and other actions by the alliance and the U.S., such as refusal to ratify the adapted CFE Treaty pending Russia’s fulfilment of the Istanbul Commitments to Georgia and Moldova and the deployment of BMD assets in Eastern Europe, loomed large in the list of Russia’s complaints about the CFE Treaty. Nonetheless, it was Moscow’s quest to maintain dominance in its immediate neighborhood, the so-called near abroad, increasingly through the presence and employment of the Russian armed forces, that finally led it to abandon the CFE Treaty.
Keywords: Russia Foreign and Security Policy; Russia MilitaryCFE Treaty